2001
DOI: 10.4049/jimmunol.167.12.7001
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Regulation of Facilitated Glucose Transport in Human Articular Chondrocytes

Abstract: Glucose serves as the major energy substrate and the main precursor for the synthesis of glycosaminoglycans in chondrocytes. Facilitated glucose transport represents the first rate-limiting step in glucose metabolism. This study examines molecular regulation of facilitated glucose transport in normal human articular chondrocytes by proinflammatory cytokines. IL-1β and TNF-α, and to a lesser degree IL-6, accelerate facilitated glucose transport as measured by [3H]2-deoxyglucose uptake. IL-1β induces an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
3
4

Year Published

2002
2002
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(137 citation statements)
references
References 77 publications
(52 reference statements)
7
123
3
4
Order By: Relevance
“…The IL-1-dependent increase in glucose transport by ovarian cells was found to be mediated via up-regulation of GLUT3 expression (Kol et al 1997), while the IL-1-induced increase in glucose transport by porcine synovial fibroblasts depended on the up-regulation of erythrocyte GLUT1. In human articular chondrocytes, IL-1 had no effect on GLUT3 and GLUT8 expression, whereas GLUT1 and GLUT9 were up-regulated (Shikhman et al 2001). In the present study, we have shown that IL-1, TNF-and IFN-down-regulate the expression of GLUT8 in Leydig cells.…”
supporting
confidence: 49%
“…The IL-1-dependent increase in glucose transport by ovarian cells was found to be mediated via up-regulation of GLUT3 expression (Kol et al 1997), while the IL-1-induced increase in glucose transport by porcine synovial fibroblasts depended on the up-regulation of erythrocyte GLUT1. In human articular chondrocytes, IL-1 had no effect on GLUT3 and GLUT8 expression, whereas GLUT1 and GLUT9 were up-regulated (Shikhman et al 2001). In the present study, we have shown that IL-1, TNF-and IFN-down-regulate the expression of GLUT8 in Leydig cells.…”
supporting
confidence: 49%
“…These authors demonstrated that treating 3T3-L1 adipocytes with recombinant murine IL-6 for 5 h increased basal glucose transport by ~20%. An increase in IL-6-stimulated basal glucose transport has also been observed in both smooth muscle [67] and chondrocytes [68], although this effect is not always seen, as two studies have found no effect of IL-6 on basal glucose transport in 3T3 L1 adipocytes [55,69].…”
Section: Interaction Between Il-6 and Glucose Transport In Vitromentioning
confidence: 92%
“…One plausible explanation for this observation is an increase in the translocation of preexisting GLUT1 protein from subcellular compartment to the cell membrane 20 in an extremely hypoxic environment. It is also possible that other glucose transporters, such as GLUT3 and GLUT9, which have recently been shown to be expressed in chondrocytes, 14,34 are involved in this process. GLUT3 is known to be a high-affinity glucose transporter, 13 and could have a role in regulating glucose transport under such stimuli where chondrocytes have a very high metabolic demand to maintain their matrix synthesis function.…”
Section: Discussionmentioning
confidence: 99%